1993
DOI: 10.1161/01.cir.87.2.526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-CD18 antibody on myocardial neutrophil accumulation and infarct size after ischemia and reperfusion in dogs.

Abstract: Although PMN accumulation contributed to reduced postischemic microvascular perfusion, it caused insufficient additional myocardial cell death to measurably affect infarct size in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(50 citation statements)
references
References 39 publications
1
48
0
1
Order By: Relevance
“…Although several experimental studies have shown that inhibition of leukocyte adhesion by treatment with an anti-CD18 antibody can reduce myocardial infarct size, 24,25 a recent report in humans did not show the effect of anti-CD18 antibody treatment on infarct size. 26 The discrepancy between the results of the experimental and human studies may be attributed to the optimal timing or dosage of administration.…”
Section: Discussionmentioning
confidence: 96%
“…Although several experimental studies have shown that inhibition of leukocyte adhesion by treatment with an anti-CD18 antibody can reduce myocardial infarct size, 24,25 a recent report in humans did not show the effect of anti-CD18 antibody treatment on infarct size. 26 The discrepancy between the results of the experimental and human studies may be attributed to the optimal timing or dosage of administration.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence from several lines of investigation suggests that inflammation is an important functional contributor to the pathogenesis of ischemic myocardial injury. For example, in animal models, neutrophil depletion with antibodies (128) or physical filtering (34,61), as well as the inhibition of neutrophil adhesion with anti-CD18 monoclonal antibody (142), all substantially reduce injury after reperfusion. In addition, interventions targeted at a variety of specific inflammatory mediators have demonstrated benefits in I/R injury, including complement depletion (96) or lipoxygenase inhibitors (133), or antibodies to the proinflammatory cytokine IL-1 (60).…”
Section: Tlr Signaling Mediates Myocardial I/r Injurymentioning
confidence: 99%
“…Accordingly, early bolus application of adhesion antagonists, eg CD18 antibodies or selectin antagonists, reduces myocardial detriment after 3-6 h of reperfusion. 4,5 However, improvement of myocardial function after anti-adhesive therapy fades over time, and is maintained only in animals receiving continuous antiadhesive treatment. 6,7 Consistent with these observations, postischemic PMN adhesion occurs in an immediate or delayed manner:…”
Section: Introductionmentioning
confidence: 99%